Bond and Sukuk Interconnectedness Analysis: A Comparative Study between GCC and MENA Countries Amidst Global Crises - Ganjar Primambudi; Muhammad Rizky Siddiq; Muhammad Revi Rafsanzani (Universitas Muhammadiyah Yogyakarta, 2023)
This paper aims to analyze the interconnectedness between Bond and Sukuk markets in the Gulf Cooperation Council (GCC) and Middle East and North Africa (MENA) countries. This study utilized the TVP-VAR extended joint connectedness method. The observed period was from January 2020 to October 2023, encompassing significant global events such as the COVID-19 pandemic, the Russia-Ukraine war, and the Israeli-Palestinian war. The results show the interconnectedness of bond and sukuk markets in both regions by 73% (based on TCI). The Bond and Sukuk instruments in MENA act as transmitters, while Bond and Sukuk in GCC act as receivers. The study suggests that the Sukuk in GCC and MENA may serve as an attractive option for diversified assets compared to Bonds. Additionally, the paper highlights structural changes and market dynamics during the crisis period that affected financial stability in both regions.Â The anticipated contribution of this study is to enriching the global economic in term of financial literature and offering policy insight to manage risks and improve financial system resilience in GCC and MENA countries.